Exploring Legal Vacuum in Tax Dispute Claims: A Study of Tax Insurance Regulatory Asymmetry in M&A Transactions - Mia Rasmiaty (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The absence of tax insurance regulations in Law No. 40/2014 and POJK creates legal uncertainty that triggers post-M&A disputes. The unclear scope of “tax risk” coverage has the potential to increase the fiscal burden and losses of companies. This study aims to identify and analyze gaps in tax insurance regulations within the Indonesian legal framework. The results are expected to formulate recommendations for amendments to the Insurance Law, technical guidelines from the OJK-DJP, and standard policy clauses. The research method uses a normative legal approach with statutes, conceptual analysis, and case studies. This study found that the absence of specific regulations on tax insurance in the Insurance Law and POJK creates uncertainty regarding coverage after M&A. The lack of clarity in the definition of “tax risk” and the absence of mandatory clause guidelines trigger potential disputes and fiscal losses for businesses. Therefore, amendments to the Insurance Law, integrated technical guidelines from the OJK and DJP, and tax insurance contract standards are needed to ensure legal certainty and investment stability.